EVALUASI KESIAPAN DIGITAL MAHASISWA DALAM PEMBELAJARAN MATEMATIKA BERBASIS TEKNOLOGI DI ERA DIGITAL - Mutia Eliza (EDU RESEARCH, 2023)
This study aims to evaluate students' digital readiness in dealing with technology-based mathematics learning in the digital era, given the demands of digital transformation that affect various aspects of higher education, including mathematics teaching. Students' digital readiness in this study is defined as the ability to access technology, digital literacy, and adaptability to technology-based learning tools. This research used a qualitative approach with a case study method, where data were collected through in-depth interviews and questionnaires to 50 students from the Mathematics Education study program at a university in Indonesia. Data were analyzed using thematic analysis technique to identify patterns and main themes related to students' digital readiness. The results showed that most students have good access to basic digital tools, such as laptops and smartphones, as well as the internet. However, there are challenges in accessing mathematics-specific software that supports concept visualization and interaction in technology-based learning. In addition, students' digital literacy is at an intermediate level, with some students still finding it difficult to utilize mathematics-specific learning software and applications. The main factors influencing digital readiness include access to technology, digital literacy competence, and students' experience in using technology-based applications. Obstacles faced by students include limitations in using specialized software and low understanding of digital literacy in the context of mathematics learning.